The risk of major osteoporotic fractures with GLP-1 receptor agonists when compared to DPP-4 inhibitors: A Danish nationwide cohort study - Al-Mashhadi, Zheer Kejlberg; Viggers, Rikke; Fuglsang-Nielsen, Rasmus; Vestergaard, Peter; Gregersen, Søren; Starup-Linde, Jakob (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes mellitus (T2D) is associated with an increased fracture risk. There is little evidence for the effects of glucagon-like peptide 1 receptor agonists (GLP-1RA) on fracture risk in T2D. We aimed to investigate the risk of major osteoporotic fractures (MOF) for treatment with GLP-1RA compared to dipeptidyl peptidase 4 inhibitors (DPP-4i) as add-on therapies to metformin. Methods: We conducted a population-based cohort study using Danish national health registries. Diagnoses were obtained from discharge diagnosis codes (ICD-10 and ICD-8-system) from the Danish National Patient Registry, and all redeemed drug prescriptions were obtained from the Danish National Prescription Registry (ATC classification system). Subjects treated with metformin in combination with either GLP-1RA or DPP-4i were enrolled from 2007 to 2018. Subjects were propensity-score matched 1:1 based on age, sex, and index date. MOF were defined as hip, vertebral, humerus, or forearm fractures. A Cox proportional hazards model was utilized to estimate hazard rate ratios (HR) for MOF, and survival curves were plotted using the Kaplan-Meier estimator. In addition, Aalen’s Additive Hazards model was applied to examine additive rather than relative hazard effects while allowing time-varying effects. Results: In total, 42,816 individuals treated with either combination were identified and included. After matching, 32,266 individuals were included in the main analysis (16,133 in each group). Median follow-up times were 642 days and 529 days in the GLP-1RA and DPP-4i group, respectively. We found a crude HR of 0.89 [0.76–1.05] for MOF with GLP-1RA compared to DPP-4i. In the fully adjusted model, we obtained an unaltered HR of 0.86 [0.73–1.03]. For the case of hip fracture, we found a crude HR of 0.68 [0.49–0.96] and a similar adjusted HR. Fracture risk was lower in the GLP-1RA group when examining higher daily doses of the medications, when allowing follow-up to continue after medication change, and when examining hip fractures, specifically. Additional subgroup- and sensitivity analyses yielded results similar to the main analysis. Conclusion: In our primary analysis, we did not observe a significantly different risk of MOF between treatment with GLP-1RA and DPP-4i. We conclude that GLP-1RA are safe in terms of fracture.